Correlation Between English Achievement, Vocabulary Mastery, and Self-Motivation Among Students 2nd Semester in Institute Shanti Bhuana Bengkayang - Tawarik, Oxtapianus; Hendri, Pebrianus; Yonas, Apolonius (Journal of Educational Learning and Innovation (ELIa), 2024)
Abstract. The study intends to find out the link between student English Achievement, Vocabulary Mastery, and self-motivation. This research is done using a correlational design. The sample of this research is the second-semester students of ISB (Institute Shanti Bhuana College) Bengkayang, West Kalimantan, in the academic year 2023-2024. This research is correlational research utilizing quantitative data-gathering procedures and quantitatively descriptive and inferential statistics. The tool employed in this study is the score of vocabulary mastery and self-motivation test section to evaluate student vocabulary and self-motivation, whereby manually (test Item validity and reliability) validity and relativity to both test tools have been carried out. To analyze the data in the study, the author uses descriptive statistics (value of individual or individual score, value of average or mean score) and inferential statistics (linear regression correlation formula) to calculate the variable of English achievement, vocabulary mastery, and self-motivation. The findings of this study demonstrate that for the degree of self-motivation and vocabulary mastery, Students in ISB were at a good level. The researchers also observed that there was a positive link between English achievement, vocabulary mastery, and self-motivation of students in the second semester at ISB in the academic year of 2023-2024 with a correlational significance of 0.462. Based on the results of the study, it may be concluded that English accomplishment, vocabulary mastery, and self-motivation in pupils have a positive link, which means the greatest degree of mastery of vocabulary and self-motivation is also high. Therefore, the instructor has to consider this kind of aspect that might impact the learning accomplishment, which plays an extremely crucial role.